Analysis of The Influence of MSMEs and Open Unemployment on Economic Growth in Jambi Province - Mayesti, Indria; Said, Mukti; Halim, Abd; Pasla, Bambang Niko (Jurnal Prajaiswara, 2024)
Introduction/Main Objectives: This study analyzes the influence of MSMEs and open unemployment on economic growth in Jambi Province. The objectives are to examine: (1) the development of MSMEs, open unemployment, and economic growth in Jambi Province, and (2) their influence on economic growth. Research Methods: A quantitative descriptive analysis method was used to assess the data. Finding/Results: Economic growth in Jambi Province has been relatively stable, averaging 4.25% annually, with GDP rising from 111,766.13 in 2013 to 169,268.80 in 2023. MSME business units also showed stable growth, averaging 14.69% per year, increasing from 81,552 in 2013 to 176,051 in 2023. Open unemployment rates were more volatile, averaging 2.70% annually, rising from 69,760 in 2013 to 85,576 in 2023. The t-test results indicate that MSMEs (X1) have a significant positive effect on economic growth, with a t-count value of 3.345 exceeding the t-table value of 1.812 and a significance of 0.010. Conversely, the open unemployment variable (X2) showed no significant effect, with a t-count of 1.480 below the t-table value and a significance of 0.177. Conclusion: MSMEs significantly contribute to economic growth in Jambi Province, while open unemployment does not exhibit a significant impact. This research underscores the importance of strengthening MSME development to drive sustainable economic growth in the region.